Using Arachis pintoi leaf extracts in biosynthesis of silver nanoparticles for improving the vase life of cut carnation (Dianthus caryophyllus L.) - Lap Xuan, Tran; Ba Le, Le; Anh Tu, Le Thi (Vietnam Journal of Biotechnology, 2020)
A biological method for synthesizing silver nanoparticles (SNPs) using the leaf extracts of Arachis pintoi Krapov. & W.C. Greg. was developed.  The optimum conditions of input materials were found with leaf autoclaving in 15 min, 20 g fresh leave, and 4 mM of silver nitrate (AgNO3). To study the role of time, temperature, and solution pH of the reaction, varying time reaction (5, 30, 60, 90, 120, 150, and 180 min), temperature reaction (10, 20, 30, 40, and 50oC) and pH of the solution (1, 3, 5, 7, 9, and 11) were investigated. The optimal biosynthesis conditions were achieved in 180 min of reaction time at 50oC and pH 11. The obtained nanoparticles have spherical and oblong in shape with average size of 26.4 nm. The SNPs in 4 concentrationss (5, 15, 25, and 35 ppm) combined with and without 2% sucrose extended vase life, enlarged flower diameter, and maintained increase the relative fresh weight with vase solution uptake rate. SNPs inhibited significantly the bacterial growth in the stem end and vase solution, reduced the blockage in stems and therefore promoted the postharvest quality of carnation cut flowers. Out of the treatments, administration of 5 ppm SNPs with 2% sucrose of vase solution gave the best results for all parameters. The biosynthesis SNPs could be applied as a promising preservative solution for carnation cut flowers.